2003
DOI: 10.1021/bi0346446
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Human Peptide Deformylase:  Implications for Antibacterial Drug Design

Abstract: Ribosomal protein synthesis in eubacteria and eukaryotic organelles initiates with an N-formylmethionyl-tRNA(i), resulting in N-terminal formylation of all nascent polypeptides. Peptide deformylase (PDF) catalyzes the subsequent removal of the N-terminal formyl group from the majority of bacterial proteins. Deformylation was for a long time thought to be a feature unique to the prokaryotes, making PDF an attractive target for designing novel antibiotics. However, recent genomic sequencing has revealed PDF-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 33 publications
2
85
0
Order By: Relevance
“…HsPDF were released (44). Seven of the thirteen ORFs of the human mitochondrial genome are predicted to be substrates of HsMAP1D, according to the known rules of MAP substrate selectivity (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HsPDF were released (44). Seven of the thirteen ORFs of the human mitochondrial genome are predicted to be substrates of HsMAP1D, according to the known rules of MAP substrate selectivity (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…1 and Refs. 7 and 9), the possible existence of an active peptide deformylase in animals has been a controversial issue (6,7,13,44). One objection raised was that the sequences of mitochondrially encoded proteins from mammals indicate that their Fo groups are retained, whereas this is not the case for the corresponding proteins of plant mitochondrial genomes (see data compiled in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Two PDFs have been identified in plants: mitochondrion-targeted PDF1A and PDF1B, which are targeted to both mitochondria and plastids (Giglione et al, 2000;Dirk et al, 2001). Only PDF1A has been found in humans and other animals (Giglione et al, 2000;Nguyen et al, 2003;Serero et al, 2003;Lee et al, 2004), and a PDF3 was identified in trypanosomatids (Bouzaidi-Tiali et al, 2007). Note that the many proteins encoded by the nuclear genome, which are further imported in the plastids, are not processed by the chloroplastic NME (cNME) but rather by a dedicated transit stromal peptidase.…”
Section: Introductionmentioning
confidence: 99%
“…Peptide deformylase is a metalloprotease involved in the posttranslational deformylation of N-terminal methionine residue of newly synthesized proteins [29]. The expression of chloroplast peptide deformylase 1A was significantly reduced in all virus infected P. Amabilis leaves, especially in ORSV-infected leaves, suggesting that viral infection has significant impact on protein modification in P. amabilis, and the symptom of chlorotic stripes in infected leaves probably resulted from the dramatically reduced expression of peptide deformylase 1A in chloroplasts.…”
Section: Proteins Regulated By All Infection Treatment With Similar Amentioning
confidence: 99%